Improving Academic Achievement of Makassar Tourism Polytechnic Students in Collaborative Strategies Reading - Windy Puspitasari Suparto; Amirullah Abduh; Muhammad Basri (Proceeding of International Conference on Islamic Boarding School, 2025)
Abstract This research aims to describe the impact of collaborative strategies reading on the academic achievement of students at Makassar Tourism Polytechnic. The present study used a qualitative descriptive design to examine the cooperative reading in collaborative strategic reading effects on academic achievement at Makassar Tourism Polytechnic. This study uses qualitative research, which is best because it examines the in-depth experience and perceptions of participants on collaborative strategic reading. This research uses the method of interviews and focus group discussions with students at Makassar Tourism Polytechnic. The purposeful sampling technique is used to select 12 students in different programs of this institution who are familiar with collaborative strategic reading.